Free Online Graphic Design Software: Canva versus Adobe Express. - Barth, Jess (Information Technology & Libraries, 2025)
The article compares two popular free online graphic design programs, Canva and Adobe Express, highlighting their features, strengths, and weaknesses for library staff creating marketing materials. Canva is noted for its user-friendly interface, extensive template library, and ease of use, making it a long-standing favorite among amateur designers. In contrast, Adobe Express offers more advanced AI features and a unique QR code generator, but its frequent updates can lead to user frustration. Ultimately, the choice between the two programs may depend on individual preferences and specific design needs, as both have evolved to offer similar functionalities over time.